Real-time germanium-doped optical fibers for clinical computed tomography dosimetry - Sarhan, H.G.; Saini, S.M.; Bahari, N.M.; Bradley, D.A. *; Zubair, H.T.; Basaif, A.; Oresegun, A.A.; Rashid, H.A. Abdul; Noor, N. M. (Elsevier, 2023)
In studies focusing on the practice of clinical computed tomography (CT) a particular concern has been that of delivering unnecessary dose to patients and with it the added risk for radiation-induced cancers. For a CT system, present work has investigated the dosimetric characteristics of a Ge-doped optical fiber real-time dosimetry system (model LS-2000, Lumisyns), measuring beam quality, exposure linearity and exposure duration accuracy. For comparison, the study has used a RaySafe X2 test device (Unfors RaySafe) and a Black Piranha (RTI) QA meter. Irradiations were made using a Somatom Definition Flash dual-source 128-slice CT scanner (Siemens Healthcare). The LS-2000, RaySafe X2, and Black Piranha sensors were exposed to beams energized at accelerating potentials ranging from 80 to 140 kVp, with tube current-time products from 50 to 300 mA, and exposure durations from 750 to 2000 ms. Constant signal responses from the LS-2000 have been obtained, measured in respect of beam quality, exposure linearity, and time accuracy. In respect of accuracy of beam quality, the RaySafe X2 and Black Piranha maximum deviations were 1% and 5%, respectively; the coefficients of linearity of RaySafe, Black Piranha and LS-2000 are 1%, 0.4% and 1.4%, respectively; the maximum deviation for the time accuracy test for the three sensors are 0.5%, 2% and 1.3%, respectively. Evaluation of the LS-2000 real-time dosimetry system with a Ge-doped optical fiber scintillator points to potential for its use in clinical CT dosimetry.